(untitled) (Asian Journal of Medical Sciences, 2017)
The present attempt is to review the research articles concerning to eating disorder/ and or eating behavior on anthropological approach from West Bengal, India. The review, concentrated on the five published research work (between 2014 and 2016) including a review article (funded by University of Calcutta) mostly funded from Biological Anthropology unit of the Statistical Institute, Kolkata India. Most of the studies, concerned with socio demographic concomitants particularly, without addressing the major issues related to the well known insight of genetics of eating disorder /and or eating behavior. Moreover, the review article (2016) on Eating Behaviours and Body Weight Concerns among Adolescent Girls attempted to find out the probable factors which are devoid of any genetic study on eating behaviours and body weight concerns among the adolescent. Most of the research article miserably failed either to justify the research article title or ended up with much known facts. Under this circumstances, the present review is the dual endeavor firstly, earnest plead to the researcher to avoid the over simplification concerning research on eating disorder /and or eating behavior and on the other hand, to sketch a probable direction of the research for the scholars, who might have inclination to undertake such an important research issue in this century. Asian Journal of Medical Sciences Vol.8(2) 2017 14-19